How much calcium does an Indian postmenopausal woman need? - Meeta Meeta (Wolters Kluwer Medknow Publications, 2022)
Calcium is needed for many biological processes. The serum concentration is of calcium is regulated very finely. The absorption of calcium and excretion maintains the calcium balance. Net calcium excretion must be replaced, but the amount of calcium needed has been debated for decades. The debate is what is the adequate calcium in Indian postmenopausal women to maintain bone health and as an intervention to prevent and treat osteoporosis. In this article experts give their opinion on the increase in the Recommended Dietary Allowance (RDA) of the ICMR 2020 committee. Based on the present evidence, the Indian menopause Society guidelines 2020, retains the ICMR 2010 recommendation of 800 mg of calcium as RDA until new Indian data emerges. The positive impact of increasing calcium and vitamin D intake is most evident in calcium-deficient individuals.